Mining Email Social Networks in Postgres - Bird, Christian (Proceedings of the Third International Workshop on Mining software repositories (Challenge Track), 2006)
Open Source Software (OSS) projects provide a unique opportunity to gather and analyze publicly available historical data. The Postgres SQL server, for example, has over seven years of recorded development and communication activity. We mined data from both the source code repository and the mailing list archives to examine the relationship between communication and development in Postgres. Along the way, we had to deal with the difficult challenge of resolving email aliases. We used a number of social network analysis measures and statistical techniques to analyze this data. We present our findings in this paper.